2023
DOI: 10.1038/s41598-023-37019-x
|View full text |Cite
|
Sign up to set email alerts
|

Improving recycling sorting behaviour with human eye nudges

Abstract: This paper tests whether visual nudges help direct attention towards existing instructions designed to increase waste sorting accuracy. The study was conducted in a quasi-experimental setting over a period of 9 weeks in two buildings of a large UK university campus. Two treatments on recycling behaviour were tested against a control group: one considered the impact of visual nudges in the form of human eyes; the other one combined human eye with pre-existing sorting instructions. Results show that for mixed re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Empirical studies have shown that displaying an image of "Watching Eyes" can increase prosocial behavior (1)(2)(3)(4)(5), reduce littering in public spaces (1,4,6) and improve waste sorting (7)(8)(9). In the study described here, around 2000 households in the Frankfurt district of Riedberg were each sent a sticker and a tag with images of "Watching Eyes" (male eyes, neutral expression) to place on or near the residual waste bin in their own kitchen or on the outside waste bin for a period of two weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical studies have shown that displaying an image of "Watching Eyes" can increase prosocial behavior (1)(2)(3)(4)(5), reduce littering in public spaces (1,4,6) and improve waste sorting (7)(8)(9). In the study described here, around 2000 households in the Frankfurt district of Riedberg were each sent a sticker and a tag with images of "Watching Eyes" (male eyes, neutral expression) to place on or near the residual waste bin in their own kitchen or on the outside waste bin for a period of two weeks.…”
Section: Introductionmentioning
confidence: 99%